Analysis of a Multiple Supply Voltage Floorplan Considering Voltage Drop and Electron Migration Risk - B, Srinath; Aruna priya, P; Kasliwal, Chirag (International Journal of Engineering and Technology, 2018)
In Contemporary Integrated Circuits (IC), the Voltage drop in the power rails and Electron migration risk (EM) due to high current densities are the most important factors degrading the reliability of the chip. The effect of these factors leads to an imbalance in the flow of charge carriers and voids in interconnects. This paper resolves the above issues, through analyzing and predetermining it in a Multiple Supply Voltage (MSV) design during the floorplanning stage. Simulations were carried out in Cadence digital Encounter system with 180nm technology for the circuit net list of 8 point FFT (Fast Fourier Transform) and FIR filter. Results show that floorplanning scheme is powerful in reducing 100% of voltage drop and 50% of EM risk in the chip as compared to previous works.Â Â